Urgensi Legislasi Pelaksanaan mandat UUD 1945 Mengantisipasi ASEAN Economic Community 2015 - Arundhati, Gautama Budi; Martua Samosir, Samuel Saut; Chandra, Ratih Listyana (Jurnal Konstitusi, 2014)
Societal welfare is the achievement that should be supported by Government which essentialy has the obligation for the societal welfare through the arrangements within the scope of authority under the mandate of the preamble and articles of   the Indonesian Constitution of 1945 and relevant laws. The mandate of ASEAN Charter, which was ratified by House of Representative by Law Number 38 of 2008 concerning Ratification of the Charter of the Association of Southeast Asian Nations, is not an opponent of the Constitution of 1945 in terms of societal welfare, as long  as the legislation is implemented on the right way, which can protect Indonesian. The legislative action must reflect the needs and the factual conditions of Indonesian. Regulation relating to the implementation of the ASEAN Charter should always be accompanied by exemption or exception to the path of liberation from the regional competition law which is a logical consequence of the free market of ASEAN in some fields.